PENGARUH POTENSI PARIWISATA TERHADAP PENYERAPAN TENAGA KERJA SEKTOR PERHOTELAN DI 9 KABUPATEN/KOTA PROVINSI JAWA TIMUR TAHUN 2012-2015 - Ghaniy Sanaubar; Wahyu hidayat; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2017)
The research is aims to know the influence of labor absorption on the potential of tourism in 9 City/Regency of East Java Province, variables are examined included number of hotels (X1), number of rooms (X2),number of domestic tourists (X3),number of foreign tourists (X4) and the number of UMK (X5). The analysis tool used is multiple linear regression analysis of the data panel in the span of 4 years. The results is show that the number of variables hotels, rooms, domestic tourists, foreign tourists are simultaneously influence with probability 0.0000 < α = 0.05,  whereas the number of UMK has no effect and could significantly explained. The amount regression coefficients of number of hotels, rooms, domestic tourists, foreign tourists and the number of labor absorption affect UMK by 99%. As for the remaining 1% is explained by variables outside of the model. Keywords: Labor Absorption, The Number of Hotels, The Number of Domestic Tourists, The Number of UMK.